This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ( x 1 x ) f ( x 1 ) f ( x 1 ) f ( x ) = 1 (1 0) f (1) f (1) f (0) = 1 (1 0)( 0.4597) 0.4597 1 = 0.6851 , x 3 = x 2 ( x 2 x 1 ) f ( x 2 ) f ( x 2 ) f ( x 1 ) = 0.6851 (0.6851 1) f (0.6851) f (0.6851) f (1) = 0.6851 (0.6851 1)(0.0893) 0.0893 ( 0.4597) = 0.7363 , and so on. Using a calculator is not very efcient and will lead to rounding errors. A better way to implement the algorithm is with a computer. Listing 6.1 below shows the code (secant.java) or solving cos x = x with the secant method, using the Java programming language:...
View
Full
Document
This note was uploaded on 01/21/2012 for the course MAC 1130 taught by Professor Dr.cheun during the Fall '11 term at FSU.
 Fall '11
 Dr.Cheun
 Calculus, Addition

Click to edit the document details